Optimizing Marketing Strategies with Big Data, AI, and Technology: Its Impact on Business Innovation and Economic Growth and in the Digital Market - Ahmadi, Dedy; Ainurrofiqie, Ainurrofiqie (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
Digitalization and technological advancements have brought about a major change in marketing strategies in the digital age. Big Data, Artificial Intelligence (AI), and other modern technologies are key elements in creating business innovation and driving economic growth. This research aims to analyze the optimization of marketing strategies using Big Data, AI, and technology, as well as their impact on business and economic innovation in the digital market. This study uses a descriptive-qualitative method with a literature study approach to analyze the role of Big Data, Artificial Intelligence (AI), and technology in optimizing marketing strategies, business innovation, and economic growth in the digital market. Meanwhile, the results of the analysis show that the application of Big Data allows companies to understand consumer behavior in depth, while AI supports service personalization and marketing process automation. The integration of this technology not only improves operational efficiency, but also creates a new business model that is adaptive to market needs. In addition, the application of this technology contributes to economic growth by increasing productivity and creating new added value in the digital sector. However, the implementation of Big Data and AI faces challenges, such as high implementation costs, data privacy concerns, and limited access to technology. Therefore, technology-based marketing strategies require a balanced approach between innovation and ethics. This research contributes to understanding the role of technology in building business competitiveness and maximizing the potential for economic growth in the digital era.